2020
DOI: 10.5811/westjem.2019.10.43055
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Hospital Utilization of Tranexamic Acid in Civilian Adult Trauma Resuscitation

Abstract: Introduction: Patients with trauma-induced coagulopathies may benefit from the use of antifibrinolytic agents, such as tranexamic acid (TXA). This study evaluated the safety and efficacy of TXA in civilian adults hospitalized with traumatic hemorrhagic shock. Methods: Patients who sustained blunt or penetrating trauma with signs of hemorrhagic shock from June 2014 through July 2018 were considered for TXA treatment. A retrospective control group was formed from patients seen in the same past five years who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These large sample sizes were identical in terms of demographics and injury severity. The sample sizes of the propensity score-based matched-pairs analysis were up to 8 times larger than prior reported studies [ 31 33 ], reaching a fifth of the patients included in CRASH 2 [ 20 ]. Therefore, the findings add knowledge to the ambiguous data on prehospital TXA use in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…These large sample sizes were identical in terms of demographics and injury severity. The sample sizes of the propensity score-based matched-pairs analysis were up to 8 times larger than prior reported studies [ 31 33 ], reaching a fifth of the patients included in CRASH 2 [ 20 ]. Therefore, the findings add knowledge to the ambiguous data on prehospital TXA use in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…However, the meaningfulness of these possibly distorted results is questionable, and their impact on heterogeneity when pooling data for overall mortality needs to be considered. Information on age, sex, or ISS was missing in several RCTs 2,13,14 and observational studies [16][17][18]35,40 ; their impact on heterogeneity is thus unknown. Moreover,…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies 3,14,19,[21][22][23][24][25]30,32,33,37 revealed higher and 8 studies 2,4,13,18,20,28,36,39 revealed lower incidences of thromboembolic events for tranexamic acid treatment compared with the control cohort. Three studies 26,34,35 could not find any association (RR, 1.00) between tranexamic acid administration and thromboembolic events. It was not possible to resolve heterogeneity through the analysis of RCTs only (I 2 = 59%; P = .03).…”
Section: Association Between Tranexamic Acid and Thromboembolic Event...mentioning
confidence: 93%
See 1 more Smart Citation
“…A number of studies have previously demonstrated that early administration of TXA either in prehospital care or ED could significantly reduce mortality in different time points (6 hours to 28 days). 36,37 We have deliberately avoided direct comparison with ED studies as time of administration is an uncontrolled variable across the two clinical arenas. The evidence from both CRASH-2 and WOMAN trials show TXA efficacy decreases over time and by 90 minutes may be of reduced benefit.…”
Section: Discussionmentioning
confidence: 99%